TELA’AH KONSEP PENDIDIKAN IBADAH DALAM AL-QUR’AN - Didi Maslan (Nizham Jurnal Studi Keislaman, 2023)
Islam views that worship education is one of the priorities that must take precedence over teaching life skills for a child. It's just that the misunderstanding of parents and teachers often makes the purpose of instilling religious education not produce the expected results. This happens due to a lack of understanding by parents and teachers regarding religious education, the foundation of which is already in the Qur'an. This paper is intended to discuss the concept of worship education in the Qur'an. The method used in collecting the required data is the literature study method by collecting literature related to the contents in this paper, both from books, journals and digital literature such as the Maktabah Syamilah.